STUDENT RESPONSES TOWARD COMIC AS AN INSTRUCTIONAL MEDIA - Shinta Rani Juwita Putri; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Learning that does not involve students actively causes a lack of balance in students' cognitive, affective and psychomotor abilities, so to solve these learning problems, it is necessary to improve learning media to make it easier for students to remember and analyze a lesson, one of them with e-comic media. This study aims to determine student responses to e-comic on the excretory system material based on cognition, affection, and conation aspects. The research method used is descriptive with a survey approach. The sample in this study was students of class XI IPA SMA, which consisted of 4 classes with 100 students. Data collection techniques in this study using a questionnaire. Data analysis uses questionnaire validation and calculates the percentage of total responses. The results showed that the average percentage of student responses to e-comic learning media in the cognitive aspect was 91%; the affective aspect was 89%; and in the conation aspect was 87.1%; each of the three aspects is categorized as very positif.